1632 Improving Excision Margins in Skin Oncology. (12th October 2021) - Ibrahim, Y; Li, Z; Vijayasurej, K; Malik, M; Jones, E; Tang, L
Abstract: Aim: There are 152, 000 new non-melanoma skin cancer (NMSC) cases in the UK every year, and excision and reconstruction of basal cell carcinomas (BCCs) and squamous cell carcinomas (SCCs) form a significant part of the clinical workload in plastic surgery. In this quality improvement project, we aimed to identify and improve our unit's compliance of guidelines for excision margins for NMSCs. Method: A retrospective audit was undertaken in June 2020 to determine compliance with British Association of Dermatology and local guidelines on excision margins for NMSCs. A repeat audit was undertaken in October 2020 following quality improvement interventions. Results: The first audit cycle examined 66 lesions in total. Guidelines were met in 53% (BCCs) and 50% (SCCs) of lesions. 12% of lesions had unclear documentation of margins. 16 lesions had margins that were too small as according to the risk factors present. These findings were presented to the department, and a new operative note template specifically designed for skin oncology was launched. Key audit findings were displayed along with the guidelines on posters. A repeat cycle was undertaken in October 2020, which examined 52 lesions. Significant improvement was seen with 100% documentation, and excision margin guideline compliance rate of 71% (BCCs) and 79% (SCCs). Conclusions: Adequate excision margins in skin oncology is vital to ensure complete excision and to minimise the risk of recurrence. Our project demonstrates significant improvement in excision margin compliance through the launch of a specific operative note template and information posters.